1997
DOI: 10.2105/ajph.87.5.740
|View full text |Cite
|
Sign up to set email alerts
|

US trends in nutrient intake: the 1987 and 1992 National Health Interview Surveys.

Abstract: OBJECTIVES: This study examined US trends in nutrient intake, using almost identical methods and nutrient databases in two time periods. METHODS: An extensive dietary intake questionnaire was included in supplements to the 1987 and 1992 National Health Interview Surveys. Dietary data from approximately 11,000 persons in each of those years were analyzed. RESULTS: The total and saturated fat intake and the percentage of energy from fat declined among Whites and Hispanics, but only minimal changes were seen in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 26 publications
(1 reference statement)
1
38
0
1
Order By: Relevance
“…compared with a typical Western diet, the intake of energy and the absolute intakes of fat and carbohydrates are much higher in rural as well as urban Cameroon (Ocke  et al, 1997;Bohlscheid-Thomas et al, 1997;Bingham et al, 1997;Riboli et al, 1997;Norris et al, 1997). Also the energy percentage of fat is higher than that in a Western diet, while that of protein is lower (Bohlscheid-Thomas et al, 1997;Bingham et al, 1997;Riboli et al, 1997;Norris et al, 1997). However, several decades ago, when nutrition campaigns had not yet focused on lowering the total fat intake, the energy percentage of fat was similar to that seen in Cameroon nowadays (Stephen & Wald, 1990).…”
Section: Habitual Diet In Cameroon LI Mennen Et Almentioning
confidence: 89%
“…compared with a typical Western diet, the intake of energy and the absolute intakes of fat and carbohydrates are much higher in rural as well as urban Cameroon (Ocke  et al, 1997;Bohlscheid-Thomas et al, 1997;Bingham et al, 1997;Riboli et al, 1997;Norris et al, 1997). Also the energy percentage of fat is higher than that in a Western diet, while that of protein is lower (Bohlscheid-Thomas et al, 1997;Bingham et al, 1997;Riboli et al, 1997;Norris et al, 1997). However, several decades ago, when nutrition campaigns had not yet focused on lowering the total fat intake, the energy percentage of fat was similar to that seen in Cameroon nowadays (Stephen & Wald, 1990).…”
Section: Habitual Diet In Cameroon LI Mennen Et Almentioning
confidence: 89%
“…A recent study (43) of more than 20,000 adults provides data which show that, despite attempts to promote increased consumption of dairy foods, the calcium intake of the U.S. population decreased by 5.1% between 1987 and 1992. Thus, we are unlikely to achieve intakes that approach the 1997 DRIs without food fortification.…”
Section: Resultsmentioning
confidence: 99%
“…Mean energy consumption of our good and under-reporters were 2,104 ± 215 and 2,086 ± 151 kcal, respectively, while the NHANES reference population of African-American men with a mean age of 64.5 yrs was 1,882 ± 94 kcal (23). Shimakawa et al (24) reported a mean intake of 1,731 ± 663 kcal in 1,567 AfricanAmerican men with a mean age of 54 yrs and Norris et al (25) reported a mean of 2,026 ± 140 kcal in 159 men with a mean age of 56 yrs. Even our under-reporters were able to report more of their food intake compared to comparable populations of African-American men.…”
Section: )mentioning
confidence: 99%